Assessing hazards to aviation from sulfur dioxide emitted by explosive Icelandic eruptions. Issue 24 (29th December 2014) - Schmidt, Anja; Witham, Claire S.; Theys, Nicolas; Richards, Nigel A. D.; Thordarson, Thorvaldur; Szpek, Kate; Feng, Wuhu; Hort, Matthew C.; Woolley, Alan M.; Jones, Andrew R.; Redington, Alison L.; Johnson, Ben T.; et al.
Abstract Volcanic eruptions take place in Iceland about once every 3 to 5 years. Ash emissions from these eruptions can cause significant disruption to air traffic over Europe and the North Atlantic as is evident from the 2010 eruption of Eyjafjallajökull. Sulfur dioxide (SO2) is also emitted by volcanoes, but there are no criteria to define when airspace is considered hazardous or nonhazardous. However, SO2 is a well‐known ground‐level pollutant that can have detrimental effects on human health. We have used the United Kingdom Met Office's NAME (Numerical Atmospheric‐dispersion Modelling Environment) model to simulate SO2 mass concentrations that could occur in European and North Atlantic airspace for a range of hypothetical explosive eruptions in Iceland with a probability to occur about once every 3 to 5 years. Model performance was evaluated for the 2010 Eyjafjallajökull summit eruption against SO2 vertical column density retrievals from the Ozone Monitoring Instrument and in situ measurements from the United Kingdom Facility for Airborne Atmospheric Measurements research aircraft. We show that at no time during the 2010 Eyjafjallajökull eruption did SO2 mass concentrations at flight altitudes violate European air quality standards. In contrast, during a hypothetical short‐duration explosive eruption similar to Hekla in 2000 (emitting 0.2 Tg of SO2 within 2 h, or an average SO2 release rate 250 times that of Eyjafjallajökull 2010), simulated SO2 concentrations are greater than 1063 µg/m3 for about 48 h in a small area of European and North Atlantic airspace. By calculating the occurrence of aircraft encounters with the volcanic plume of a short‐duration eruption, we show that a 15 min or longer exposure of aircraft and passengers to concentrations ≥500 µg/m3 has a probability of about 0.1%. Although exposure of humans to such concentrations may lead to irritations to the eyes, nose and, throat and cause increased airway resistance even in healthy individuals, the risk is very low. However, the fact that volcanic ash and sulfur species are not always collocated and that passenger comfort could be compromised might be incentives to provide real‐time information on the presence or absence of volcanic SO2. Such information could aid aviation risk management during and after volcanic eruptions.